Hubungan Pemberian Makanan Pendamping ASI Dengan Status Gizi Pada Bayi Umur 6 – 24 Bulan Di Puskesmas Bara-Baraya Makassar - Supardi, Nurjannah (Madu : Jurnal Kesehatan, 2023)
During the growth period, children need adequate nutritional intake to support their growth and development process. Babies aged 0-6 months get nutrition from only breast milk which is called exclusive breastfeeding. Babies over 6 months need MP-ASI to meet the nutritional needs of children. The provision of complementary feeding must be in accordance with the needs of the child both in terms of texture, amount, and frequency of feeding. This research was conducted with the aim of knowing the relationship between complementary feeding and the nutritional status of infants aged 6-24 months at the Bara-Baraya Makassar Health Center in 2018 This type of research is analytic observational with a cross sectional study approach. Total population of 60 people and a sample of 30 people. Data analysis using the Chi-Square test. The results of the study using the Chi Square test on the variable type of MP-ASI obtained a p value (0.047) meaning that there was a relationship between the type of MP-ASI and the nutritional status of the baby. the relationship between the age of the first complementary feeding and the nutritional status of the baby, the frequency of giving complementary feeding and the nutritional status of the baby was obtained by a value of p (0.002) meaning that there was a relationship between the frequency of giving complementary feeding and the nutritional status of the baby. he shape or texture of MP-ASI and the baby's nutritional status was obtained with a value of p (0.000) meaning that there is a relationship between the shape or texture of MP-ASI and the baby's nutritional status.